PENGARUH GAYA KEPEMIPINAN, BEBAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DAN STAFF PENDIDIK (TENDIK) DI MADRASAH TSANAWIYAH NEGERI 2 (MTSN 2) BANDA ACEH - Presilawati, Febyolla; G., Harbiyah; Qabri, Muhammad (JSI: Jurnal Saudagar Indonesia, 2024)
The aim of this research is to determine the influence of leadership style, workload and work environment on the performance of teachers and educational staff at Madrasah Tsanawiyah Negeri 2 (MTsN 2) Banda Aceh. The total population in this study was 57 respondents. This research data was obtained through interviews and filling in questions/questionnaires. Hypothesis testing uses multiple linear regression analysis, the results of research using determination correlation analysis are intended to determine the influence of the independent variable on the dependent variable with a correlation coefficient value of 84.4%. The results of the research show that simultaneous tests between the Leadership Style, Workload and Work Environment variables influence the performance of teachers and educational staff at MTsN 2 Banda Aceh. Then, partially, Leadership Style, Workload and Work Environment influence the Performance of Teachers and Teaching Staff (tendik) at MTsN 2 Banda Aceh.Keywords: Leadership Style, Workload, Work Environment and Performance of Teachers and Education Staff